Hydrothermal synthesis of rGO-PbBi2Se4 composite and investigation of its structural, chemical and field emission properties - Aher, Rahul; Bhorde, Ajinkya; Sharma, Priyanka; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Rondiya, Sachin; Chaudhary, Minakshi; Gopinath, Chinnakonda; Suryawanshi, Sachin; More, Mahendra; Jadkar, Sandesh (Journal of Materials Science-Materials in Electronics, 2018)
In the present study we report the one step facile synthesis of pristine lead bismuth selenide (PbBi2Se4) and reduced graphene oxide (rGO) and its composites with PbBi2Se4. Formation of pristine PbBi2Se4 and rGO-PbBi2Se4 composite were confirmed by X-ray diffraction and X-ray photoelectron spectroscopy. The surface morphology and topography investigated by using scanning electron microscopy and transmission electron microscopy revealed the formation of nano-flowers pristine PbBi2Se4. After coupling pristine PbBi2Se4 with rGO the surface morphology shows the formation of sharp vertically protruded nano-sheets/nano-flaks originated from the nano-flowers. Finally, the field emission properties of pristine PbBi2Se4 and rGO-PbBi2Se4 composite have been investigated. It has been observed that the rGO-PbBi2Se4 composite emitter exhibited excellent field emission properties with low turn-on field (similar to 2.8 V/A mu m for 10 A mu A/cm(2)), high emission current density (similar to 1288 A mu A/cm(2) at 3.9 V/A mu m) and superior current stability (similar to 4.5 h for similar to 1 A mu A) compare to pristine PbBi2Se4 emitter. Thus, the facile one step synthesis approach and robust nature of rGO-PbBi2Se4 composite emitter can provide prospects for the future development of large-area emitter applications such as flat-panel-display and vacuum micro/nanoelectronics devices.

Probing the effect of selenium substitution in kesterite-Cu2ZnSnS4 nanocrystals prepared by hot injection method - Pandharkar, Subhash; Rondiya, Sachin; Bhorde, Ajinkya; Nair, Shruthi; Aher, Rahul; Vairale, Priti; Waghmare, Ashish; Naik, Dhirsing; Waykar, Ravindra; Jadhav, Yogesh (Journal of Materials Science-Materials in Electronics, 2019)
In this paper, we report the effect of sulfur (S) substitution with selenium (Se) in CZTS nanocrystals prepared by hot injection method. The formation of kesterite-copper zinc tin sulfide (Cu2ZnSnS4, CZTS) and copper zinc tin selenide (Cu2ZnSnSe4, CZTSe) nanocrystals is confirmed by X-ray diffraction (XRD), Raman spectroscopy and transmission electron microscopy (TEM) analysis. The XRD, TEM and atomic force microscopy (AFM) analysis shows an overall increase in average crystallite size upon Se substitution. AFM images revealed an increase in root mean square surface roughness (S-q) and average surface roughness (S-a) when S in CZTS is replaced by Se. The substitution of S by Se in host CZTS narrows the optical band gap from 1.56 to 1.03 eV. The ultraviolet photoelectron spectroscopy (UPS) analysis shows shift in valence band and conduction band edge in CZTSe compared to CZTS. The photocurrent density measurement in synthesized CZTSe thin films is similar to 4 to 5 times higher than CZTS thin films. The obtained results show that CZTSe can be a promising candidate as absorber material in photovoltaic applications.

Solvothermal growth of PbBi2Se4 nano-flowers: a material for humidity sensor and photodetector applications - Aher, Rahul; Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Naik, Dhirsing; Vairale, Priti; Karpe, Smita; Late, Dattatray; Prasad, Mohit; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2019)
In the present work, lead bismuth selenide (PbBi2Se4) nano-flowers are synthesized by using a simple solvothermal method. Humidity sensor and photodetector based on PbBi2Se4 nano-flowers are fabricated on indium tin oxide (ITO) substrates and their sensing properties are investigated. Formation of PbBi2Se4 is confirmed by XRD, EDS, and XPS whereas formation of nano-flowers is confirmed by SEM and TEM analysis. XRD analysis reveals the hexagonal crystal structure of PbBi2Se4 phase with a = b = 4.22 angstrom, and c= 17.42 angstrom. The surface morphology of PbBi2Se4 clearly shows the formation of well-organized flower-like nanostructures which closely resembles the shape of Dahlia. The elemental mapping of chemical constituents obtained from SEM-EDS analysis shows uniform distribution of chemical constituents for the Pb, Bi, and Se in PbBi2Se4 nano-flowers. The PbBi2Se4 nano-flowers based humidity sensor has a typical response time of approximate to 65s and recovery time of approximate to 75 s. In case of PbBi2Se4 nano-flowers-based photodetector, the response and recovery time are observed approximate to 121 and approximate to 123 s, respectively, under visible light illumination with photoresponsivity (5 x 10(-6)), photosensitivity (2.16%), and quantum efficiency (1.5 x 10(4)). The obtained results demonstrate the potential applications of solvothermally grown PbBi2Se4 nano-flowers-based devices for humidity sensors and photodetectors. The ease of the present work is to develop novel material to obtain device quality humidity sensors and photodetectors.
Keywords: humidity sensor; PbBi2Se4; photodetector; XPS; XRD

Lead-free solid state mechanochemical synthesis of Cs2NaBi1-XFeXCl6 double perovskite: reduces band gap and enhances optical properties - Udavant, Rohini; Thawarkar, Sachin; Rondiya, Sachin; Shelke, Ankita; Aher, Rahul; Ajithkumar, Thalasseril G.; Cross, Russell W.; Dzade, Nelson Y.; Jadkar, Sandesh (Inorganic Chemistry, 2023)
Efficient and stable lead-free halide double perovskites (DPs) have attracted great attention for the future generation of electronic devices. Herein, we have developed a doping approach to incorporate Fe3+ ions into the Cs2NaBiCl6 crystal unit and reveal a crystallographic and optoelectronic study of the Cs2NaBi1-xFexCl6 double perovskite. We report a simple solid-state mechanochemical method that has a solvent-free, one-step, green chemistry approach for the synthesis of Cs2NaBi1-xFexCl6 phosphor. The analysis of powder X-ray diffraction (XRD) data determines the contraction of the lattice due to the incorporation of Fe3+ cations, and this effect is well supported by X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), Raman spectroscopy, and solid-state nuclear magnetic resonance spectroscopy (ss-NMR). The band gap is reduced with increasing Fe content owing to the strong overlap of the Fe-3d orbitals with Cl-3p orbitals and shift of the valence band maxima (VBM) toward higher energies, as confirmed by ultraviolet photoelectron spectroscopy (UPS) and density functional theory (DFT) analyses. Photoluminescence (PL) studies of Cs2NaBi1-xFexCl6 phosphors exhibit a large Stokes shift, broadband emission, and increased PL intensity more than ten times for 15% of Fe content phosphor with enhancement in the average decay lifetimes (up to 38 ns) compared to pristine Cs2NaBiCl6 DP. These results indicate that the transition of dark self-trapping of excitons (STEs) into bright STEs enhances yellow emission. XRD, UV, and thermo-gravimetric analysis (TGA) confirmed that the Cs2NaB1-xFexCl6 DPs have good structural and thermal stabilities. Our findings indicate that the doping of Fe3+ cations into the Cs2NaBiCl6 lattice is a constructive strategy to enhance significantly the optoelectronic properties of these phosphors.

Field emission performance of 2D Ti2CT x (T x = O2, F2, O-F) MXene: experimental insights and theoretical endorsement - Kakade, Prashant M.; Aher, Rahul; Kachere, Avinash R.; Cho, Jinill; Deore, Amol; Jadkar, Sandesh R.; Chauhan, Inderjeet; Kim, Taesung; Mandlik, Nandkumar T.; Kim, Ji Man; Bulakhe, Ravindra N. (ACS Applied Nano Materials, 2026)
Field emission (FE) is an important electron emission mechanism for vacuum microelectronic devices; however, conventional emitters often exhibit high turn-on fields, limited emission stability, and degradation during prolonged operation. Two-dimensional MXenes have recently emerged as promising FE materials due to their remarkable electrical conductivity, comparatively low work function, and tunnelable surface terminations. Nevertheless, most studies have focused on Ti3C2T x MXene, while other compositions such as Ti2CT x remain largely unexplored, particularly regarding the influence of surface terminal groups on their electronic and emission properties. Herein, Ti2CT x (T x = -F2, -O2, -OF) MXene was synthesized via selective chemical etching of the Ti2AlC MAX phase and investigated for its FE characteristics. The material exhibits a polycrystalline hexagonal layered structure with a high specific surface area of 349.02 m2 g-1. Ti2CT x MXene demonstrates excellent FE performance with a low turn-on field of 1.56 V mu m-1 and a threshold field of 2.0 V mu m-1 (at 10 mu A cm-2), along with a stable emission for 4 h. Density functional theory calculations further reveal that surface terminations strongly influence the electronic structure and work function, with the experimental value of 4.66 eV closely matching the -F2 termination. These results highlight Ti2CT x MXene as a promising material for stable and efficient FE applications.
Keywords: 2D Ti2CT x MXene; field emission; TDOS and PDOS; Turn-on voltage; Work function